Effect of Tribulus terrestris, ginger, saffron, and Cinnamomum on menopausal symptoms: a randomised, placebo-controlled clinical trial - Taavoni, Simin; Ekbatani, Neda Nazem; Haghani, Hamid (Menopause Review/Przegląd Menopauzalny, 2017)
Menopausal symptoms experienced by women vary widely, and while many women transition through menopause with manageable symptoms, others experience severe symptoms, which may impair their quality of life. The purpose of this study was to determine the effect of Tribulus terrestris , ginger, saffron, and Cinnamomum on menopausal symptoms. A randomised, triple-blind, controlled trial design was used for this study. The participants were 80 postmenopausal women aged 50–60 years. A demographic data form and the Menopause Rating Scale were used to collect data. The women were randomly divided into two groups, each of which received either an Aphrodit capsule or a placebo twice a day for four weeks. The two bottles looked exactly the same, so that the investigator and the participants were not aware of the contents of the bottles. Each Aphrodit capsule contained 40 mg of Tribulus terrestris , 12.27 mg of Zingiber officinale, 3 mg of Crocus sativus extract, and 11 mg of Cinnamomum zeylanicum, while the placebo capsules contained 50 mg of starch. Descriptive and inferential statistics were used to analyse the data. A statistically significant change was reported in the menopausal symptoms of the intervention group compared with the placebo group. The results of the study demonstrate that the Aphrodit capsule was effective in reducing menopausal symptoms.